Analisis Bakteriologis Kualitas Air Sumur di Kota Pekanbaru - Sayuti, Irda (Jurnal Pilar Sains, 2006)
This research for destination to know quality well water in Pekanbaru city based on sum bacteria coilform fecaland coliform non fecal on July until December of 2007 in Biologi laboratory FKIP UNRI. Take sample carryout way purposive random sampling in all 12 subdistrict there are in Pekanbam city, are Sukajadi subdistrict,Tenayan Raya, Rumbai, Marpoyan Damai, Tampan, Bukit Raya, Rumbai pesisir, Pekanbaru city, Senapelan,Sail, Payung Sekaki and Lima Puluh. Every subdistrict decide 3 lacated, take sample well with judgmentdistance place/located well from resources pollution and activity society, is : Take well water from houses tolocated neared with market (0-500 m), take well water from houses located near with Siak River and Sail River(0-500 m) and take well water from house located far from marke and River (>500 m). Procedur researchconsist of: 1) stage production medium is medium is medium kaldu laktosa (lactosa broth) and medium brilliantgreen lactose bile broth (BGLBB), 2) investigation sample with test MPN (Most probable numbu)/JPT (totalapproximation neared). Data result research analysis like descriptive, based on standardization quality watergroup B about rules quality water group B about rules quality clean water by minister of public health regulationRI No. 416/minester of public health/Per/lx/1990. From result research can conclusion that well water inpekanbaru city be pregnant coliform fecal revolve between 4,7 cell bacteria/100 ml-26,7 cell bacteria/l00 ml andcoliform non fecal revolve between 49,7 cell bacteria/100 ml- 172.7 cell bacteria/l00 ml, untill well water inPekanbaru city quality less good for used as resources clean water because already pass by maximum fromwater group B.